2016
DOI: 10.1038/srep39024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Reveals that Phosphorylation of β Carbonic Anhydrase 1 Might be Important for Adaptation to Drought Stress in Brassica napus

Abstract: Little is known about the mechanism of drought tolerance in rapeseed (Brassica napus L.). In this study, different morphological and physiological responses to drought stress were studied in three rapeseed cultivars. For the cultivar 2AF009 with high drought tolerance, comparative proteomic analyses were conducted to determine the molecular mechanism behind. Approximately 138 differentially abundant proteins (DAPs) and 1232 phosphoproteins containing 4469 phosphopeptides were identified. Furthermore, 337 phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 55 publications
1
29
0
1
Order By: Relevance
“…The hydrogen bonds of the Trp, Arg, and Tyr residues in this site are well organized to recognize the bicarbonate ion such anions as acetate or nitrate are not able to carry out all the necessary interactions with the hydrogen bonds of these amino acid residues. Tyr residues in the active site and bicarbonate binding site structures were recently found to be the key amino acids for the reversible modification by phosphorylation and nitration in response to abiotic and biotic stresses [11,12]. Such modifications allow for blocking the passage of substrate and inhibiting the activity of β-CAs under stress conditions.…”
Section: β-Casmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrogen bonds of the Trp, Arg, and Tyr residues in this site are well organized to recognize the bicarbonate ion such anions as acetate or nitrate are not able to carry out all the necessary interactions with the hydrogen bonds of these amino acid residues. Tyr residues in the active site and bicarbonate binding site structures were recently found to be the key amino acids for the reversible modification by phosphorylation and nitration in response to abiotic and biotic stresses [11,12]. Such modifications allow for blocking the passage of substrate and inhibiting the activity of β-CAs under stress conditions.…”
Section: β-Casmentioning
confidence: 99%
“…This CA was named β-CA1 by Fabre [5] in the study of CAs of β-family in Arabidopsis leaves. Later, this name started to be used to designate the corresponding stromal CAs in leaves of other plants [12,15]. This enzyme is the second after Rubisco in terms of the amount of protein in the cell (0.5-2% of the total) [106].…”
Section: Carbonic Anhydrases In Chloroplasts Of C3 Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn deficiency has also been shown to decrease CO 2 concentration that results from the decreased activity of a Zn-dependent enzyme, carbonic anhydrase (Sharma et al, 1995;Li et al, 2013;Sharma et al, 1994). Studies revealed that carbonic anhydrase is involved in a CO 2 -sensing pathway in guard cells (DiMario et al, 2017) and adaptation to drought stress (Wang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The response of g m to increasing temperature was insufficient to keep up with the CO 2 uptake, and CA‐ and/or aquaporin‐facilitated processes were proposed by Bernacchi et al () to underpin the limitation on photosynthesis at higher temperatures. In rapeseed ( Brassica napus L.), βCA1 was downregulated during drought, both at the transcriptional level and by phosphorylation of the substrate‐binding active region (Wang et al , ). Water stress has been further confirmed to have negative impacts on the activities of CA, Rubisco and photosynthesis‐related proteins in other species, including durum wheat ( Triticum durum Desf., Guliyev et al , ), coffee ( Coffea canephora Pierre ex A. Froehner, Marraccini et al , ) and grapevine ( Vitis vinifera L., Król and Weidner, ).…”
Section: Environmental Stress and Ca Activitymentioning
confidence: 99%